HUBUNGAN PENGETAUAN, MASA KERJA DAN PENGAWASAN TERHADAP PERILAKU PEMILAHAN LIMBAH MEDIS PADA TENAGA KESEHATAN DI RUMAH SAKIT HERMINA DEPOK TAHUN 2023 - Salamah, Nurul Pitriani; Nina, Nina; Yaser, Mohammad (SEKOLAH TINGGI ILMU KESEHATAN INDRAMAYU, 2024)
Introduction: Sorting waste is carried out starting from the source that produces the waste, sharps waste is collected in one container by considering whether it is contaminated or not, and solid medical waste is reused through a sterilization process. The aim of this research is to determine the relationship between knowledge, length of service and supervision on medical waste sorting behavior among health workers at Hermina Hospital, Depok in 2023. Method: This research is a quantitative study using a cross sectional approach. The population in this study were health workers such as nurses, midwives and pharmacists who worked at the Hermina Depok General Hospital with a total of 201 health workers and the sampling used in this study used the Accidental Sampling technique and a sample of 134 health workers was obtained. Results: research shows that there is a relationship between knowledge and a p value of 0.003 (p<0.05) and OR=2.958, there is no relationship between years of service with a p value of 0.181 (p>0.05), and there is a relationship between supervision and the p value of 0.001 (p>0.05) with the medical waste sorting behavior of health workers. Conclusion: Overall it can be concluded that the condition of Health Workers at RSU Hermina Depok regarding knowledge requires adequate training or socialization regarding sorting medical waste. This training should cover procedures, regulations and guidelines applicable to sorting and managing medical waste. This results in the lack of knowledge of health workers in sorting waste in hospitals which can be very serious and have a negative impact on the environment. One of the main impacts of poor waste sorting is environmental pollution, risk of injury, additional costs to hospitals